An inducible nuclear body in the Drosophila germinal vesicle. - Singer, A.B.; Gall, J.G. (Nucleus, 2011)
When living egg chambers of Drosophila are isolated in a saline solution and gently squashed between a microscope slide and coverslip, prominent nuclear bodies (1 - 20 mm diameter) can be seen inside the oocyte nucleus or germinal vesicle (GV).  These bodies do not pre-exist within the GV and are not seen in material that is fixed in paraformaldehyde before squashing.  Instead, they form spontaneously within minutes after an egg chamber is damaged and the cytoplasm is exposed to the isolation medium.  Electron microscopy shows that the bodies lack an investing membrane and consist of closely packed, irregular particles 30-50 nm in diameter.  We used GFP-tagged proteins from the Carnegie Protein Trap Library to identify 22 proteins that are either enriched in the bodies or excluded from them.  We were unable to discern common features of proteins that are concentrated in the bodies, such as isoelectric point, molecular weight, or biological process.  Induced bodies are formed in GVs of flies that are null for coilin or WDR79, proteins that are required for formation of Cajal bodies (CBs).  We performed fluorescence recovery after photobleaching (FRAP) experiments on five GFP-tagged proteins that are enriched in the bodies.  Four of the proteins regained the full pre-bleach fluorescence intensity, indicating that the contents of the bodies are in dynamic equilibrium with the surrounding nucleoplasm.  Induced nuclear bodies presumably form as a result of unusual physico-chemical changes in the Drosophila GV.  We suggest that their behavior serves as a useful model for self-assembly of nuclear bodies in general, and we discuss the possibility that similar bodies may occur normally in cells of other organisms.